Vestibular Neuritis - 10 years in retrospective - São Pedro, Ricardo (2021)
Objective: Clinical and epidemiological characterization of the hospitalized patients with vestibular neuritis (VN) in the Otorhinolaryngology department of the Hospital Garcia de Orta and evaluation of the effect of corticotherapy on the hospital stay lenght. Study design: Retrospective study. Material and methods: 124 adult patients (18 years plus) admitted with the diagnosis of VN were retrospectively analyzed between January 2010 and July 2019. 25 patients were excluded due to the presence of newly onset hypoacusis, tinnitus or neurological signs. Results: 53% of the patients we’re male and the mean age was 56 years. The incidence was highest on the first trimester of the year (31,3%). The mean length of hospital stay was 5,66 ± 3,73 days. Corticosteroid therapy throughout hospitalization did not correlate with less length of hospital stay. Conclusions: VN presents itself as an acute illness conditioning hospitalization of significant duration. Corticotherapy does not seem to affect the duration of the clinical picture in the short term.